PGA data of Antarctic carbonaceous chondrites with CI and CM affinity ... - Ebihara, Mitsuru (Mendeley Data, 2024)
At present, carbonaceous chondrites are classified into nine groups based on their chemical characteristics. Among carbonaceous chondrites, CI and CM chondrites are considered the more primitive meteorites. Currently, there are five known non-Antarctic CI chondrites, and four have been identified among Antarctic meteorites. In this study, elemental analysis was conducted on a total of twelve meteorites, focusing primarily on the major element composition, including four Antarctic CI chondrites and eight others having affinities with CI or CM but insufficiently chemically clarified. The analytical method employed in this study was neutron-induced prompt gamma-ray analysis (PGA), which shares analytical advantages similar to wet chemical analysis. Quantitative values were obtained for 15 elements: Fe, Mg, Si, S, Ni, H, Al, Ca, Cr, Mn, Co, Ti, chlorine, B, and Gd, and almost all of the main constituent elementals were quantified. Comparison with literature values, including those obtained by the wet chemical ...